Introduction: Politics in India-an overview - Kohli, Atul; Singh, Prerna (Routledge Handbook Of Indian Politics, 2013)
The study of Indian politics constitutes an exciting area of scholarship. This collection brings together some of the leading and emerging scholars of Indian politics to reflect on their respective areas of specialization. Each contribution is a self-sufficient essay that introduces readers-be they specialists or new to the subject-to a specific topic and provides references to facilitate further pursuit of the subject. These contributions 'speak' in the voice of the authors. Many of the essays here are not only distillations of prior scholarship, but also point to new directions of thinking and research. We (the editors of the volume) are responsible for inviting the contributors, but since this is a Handbook, we have not tried to impose any artificial unity; the contributions represent a variety of normative and theoretical standpoints. The minimal unity of the volume comes from the organization of the subject matter. In this introductory chapter we provide an overview of the subject-politics in India-and point to where and how individual essays of the collection fit within the broader scheme.